Quality improvement of kenaf-based tofu: effects of kenaf seed substitution, and coagulant types and concentrations on the physicochemical quality, texture profile and microstructure of the tofu - Ibrahim, Shafa’atu Giwa; Wan Ibadullah, Wan Zunairah; Saari, Nazamid; Karim, Roselina (John Wiley and Sons, 2022)
Tofu was made by substituting kenaf seed (K) with soybean (S) at 100 (positive control), 50%, 40%, 30%, 20%, 10% and 0% (negative control). The results indicated that kenaf seed substitution at all ratios significantly increased the soluble solids and protein content of the milky extracts. The yield, moisture and protein content of the tofu were significantly increased with the increase in kenaf seed substitution, while the lipid content was significantly decreased. The tofu made with kenaf seed substitution of 50%, 40% and 30% had the same protein content (43.76–45.36 g/100 g) with the positive control (45.36 g/100 g), but a significantly higher lipid content (32.00–35.75 g/100 g) than that of the positive control (27.50 g/100 g). The microstructure of the tofu revealed that only the positive control had a honey-comb structure, whilst the tofu made from kenaf seed-soybean blends had a pseudo-honey like structure. Up to 30% of soybean can be added into the kenaf-based tofu, without any negative effect on the textural and colour properties and, protein content, but significantly improved the essential amino acids content of the kenaf-based tofu. Therefore, the blend of 70K:30S ratio using 0.5 g% glucono delta-lactone as a coagulant is recommended to produce kenaf seed-soybean tofu.